NURSING STUDENTS PERCEPTION TOWARDS CARING BEHAVIOR OF CLINICAL INSTRUCTOR: A LITERATURE REVIEW - Sri Yulian Hunowu; Fitri Arofiati (The Shine Cahaya Dunia Ners, 2019)
Background: Important factors for student success are determined by the behavior of an instructor. Students understand that caring instructors clinic can make students more confident. Caring behavior is a behavior that always assists others holistically. The objective is to know the perception of the caring behavior of nursing students on the clinical instructor. Method: This literature review uses searches from the Google Scholar database, Science Direct, EBSCO. At the initial stage of the search with keywords: "Caring Instructor" AND "Nursing Students Perceptions" obtained the results of 8 international articles from the range of 2014 to 2019 that correspond to the inclusion and exclusion criteria.Results: Based on the results of the literature review of 8 articles, it was found that the caring behavior of clinical instructors can be an indicator of how caring nursing students are when they enter the profession. According to nursing students caring behavior from clinical instructor have a positive attitude towards nursing students. Students become more compassionate, feel helpful when experiencing difficulties, are more open, confident and have high learning motivation.Conclusion: Caring behavior clinical instructor is to be considered by the clinical instructor to students. This is because nursing students always looked clinical instructor as a role model in demonstrating professionalism in nursing, and can improve the caring behavior of their students. Besides that, the caring behavior of the instructor can also improve the clinical learning process to be even better. Keywords: Nursing Student Perception, Caring Behavior, Clinical Instructor